1997
DOI: 10.1080/01652176.1997.9694744
|View full text |Cite
|
Sign up to set email alerts
|

A case of autochthonous canine leishmaniasis in the Netherlands

Abstract: SUMMARYThe transmission of visceral leishmaniasis (VL) in the absence of its natural vector, the sandfly, is considered exceptional. This report describes VL in a 12-month-old dog which had never been in an area in which VL is endemic but was born in the Netherlands from a bitch that had been infected in Spain. Although the mode of transmission, via the placenta or otherwise, is unknown, it can be concluded that bitches with VL can be a source of infection for their pups, even in a sandfly-free non-endemic are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 14 publications
0
19
0
5
Order By: Relevance
“…Azotemia is not surprising in CVL, since it is recognized that kidney damage associated with the disease is almost inevitable (FERRER, 1992;DIAZ-ESPINEIRA;SLAPPENDEL, 1997). Although CVL is often characterized by hypergammaglobulinemia (polyclonal B cell response) and hypoalbuminemia (renal and/or liver failure), the electrophoresis evaluation in this work did not show significant changes in albumin and γ-globulin values.…”
Section: Discussionmentioning
confidence: 61%
“…Azotemia is not surprising in CVL, since it is recognized that kidney damage associated with the disease is almost inevitable (FERRER, 1992;DIAZ-ESPINEIRA;SLAPPENDEL, 1997). Although CVL is often characterized by hypergammaglobulinemia (polyclonal B cell response) and hypoalbuminemia (renal and/or liver failure), the electrophoresis evaluation in this work did not show significant changes in albumin and γ-globulin values.…”
Section: Discussionmentioning
confidence: 61%
“…Despite the fact that the risk of autochthonous transmission from infected dogs in the absence of sand fly vectors is low, infection has been documented in dogs with no travel history from the Netherlands, northern France, Switzerland (Slappendel, 1988;Díaz-Espiñeira and Slappendel, 1997;Teske et al, 2002), Austria (Kollaritsch et al, 1989), Germany (Gothe, 1991;Naucke and Lorentz, 2012), the United Kingdonm (Shaw et al, 2009), Hungary (Tánczos et al, 2012), Romania (Mircean et al, 2014) and Finland (Karkamo et al, 2014), but it remains questionable if transmission was due to vectors, transplacental transmission or even by direct contact. Whether autochthonous or imported cases, CanL is often diagnosed in non-endemic countries and, therefore, there is a need for clear, locally relevant guidelines directing diagnosis, treatment and management of suspected cases (Teske et al, 2002;Mattin et al, 2013).…”
Section: Canl In Non-endemic European Countriesmentioning
confidence: 98%
“…A study in Holland (Slappendel 1988) showed that 92 dogs imported from the Mediterranean area were infected but there were also two autochthonous cases. One of the latter cases was the puppy of a bitch who had become infected in Spain (Diaz-Espineira & Slappendel 1997). The review by (Slappendel & Teske 1999) should be consulted for a fuller review of the CVL records outside the endemic areas.…”
Section: Dogs and Travelmentioning
confidence: 99%